THE EFFECT OF EQUALIZING EDUCATION QUALITY ON STUDENT LEARNING OUTCOMES IN FRONTIER, OUTERMOST, AND LEAST DEVELOPED AREAS (3T) - Widyana, Aminnatul; Puspitasari, Erfina; Kusumawati, Nine Indah; Sutrisno, Zeni (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
The implementation of education in facing various issues or new challenges requires the latest efforts and innovations in handling them. The equalization of educational quality, particularly in frontier, outermost and least developed areas (known as the "3T" areas), the lack of qualified educators, uneven distribution of school equipment, low incentive funds, inadequate qualifications, and differences in educational institutions, lack of government support, poor access roads, and high education costs for residents in rural 3T communities are barriers to obtaining education in remote areas. The desire to attend school also remains a significant issue, indicating that communities in remote areas still do not consider education to be important. The method used in this article is analytical descriptive. The results obtained include: (1) the implementation and approach of learning aspects; (2) an ever-changing curriculum; (3) the need for experienced infrastructure; (4) improvement of educational programs, and; (5) improvement of learning motivation. The hope for addressing various educational challenges in remote areas is that all aspects of the community should be considered. However, there is a need for government and community involvement in overcoming all existing issues. All of these efforts are aimed at improving the equalization of educational quality in remote rural areas.